Work Motivation of employees at Saechang World Company Limited - Hrientountong, Sasiton; Wonglek, Pusit (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this research were 1) to study the level of work motivation of employees at Saechang World Company Limited. And 2) to compare the level of work motivation of employees at Saechang World Company Limited, that were categorized by the personal factors. The population was 30 personnels of Saechang World Company Limited. The instrument used for data collection was a questionnaire with an Index of item-objective congruence (IOC) between 0.67 - 1.00 and the overall reliability of 0.99. The statistics used in data analysis were percentage, mean (μ), standard deviation(σ), and hypothesis testing by compare mean. The research results were as follows: 1) The level of work motivation of employees at Saechang World Company Limited, overall, it was at a high level. When considering by each aspect found that the highest level of work motivation was the Relatedness Needs, follow by the Existence Needs, and the Growth Needs. And 2) The employees at Saechang World Company Limited, who were of different ages, overall, they had different work motivation. But the employees at Saechang World Company Limited, who were of different ages, the educational level, marriage status, work position, working experiences, and income, overall, they had no different work motivation.